The Interaction of HLA-C1/KIR2DL2/L3 Promoted KIR2DL2/L3 Single-Positive/NKG2C-Positive Natural Killer Cell Reconstitution, Raising the Incidence of aGVHD after Hematopoietic Stem Cell Transplantation - Zuo, Wei; Yu, Xing-Xing; Liu, Xue-Fei; Chang, Ying-Jun; Wang, Yu; Zhang, Xiao-Hui; Xu, Lan-Ping; Liu, Kai-Yan; Zhao, Xiao-Su; Huang, Xiao-Jun; Zhao, Xiang-Yu (Frontiers in Immunology, 2022)
NKG2C+ natural killer (NK) cell plays a vital role in CMV infection control after hematopoietic stem cell transplantation (HSCT). However, the modulation on NKG2C+ NK cell reconstitution is still unclear. NK cell education is affected by the interactions of HLA-I/killer immunoglobulin receptor (KIR). Our aim is to figure out which HLA-I/KIR interaction plays a dominant role in NKG2C+ NK education. Based on allogeneic haploidentical HSCT, we investigated the expansion and function of single KIR positive NKG2C+ NK cells via the interaction of KIR with both donor HLA and recipient HLA at days 30, 90, and 180 after HSCT. KIR2DL2/L3 single-positive/NKG2C+ cells were significantly expanded compared with KIR2DL1 or KIR3DL1 single-positive/NKG2C+ cells when donors and recipients were both HLA-C1/C1 or HLA-C1C1BW4 (p < 0.05), with higher NKp30 expression (p < 0.05). Moreover, the proportion of single KIR positive NK cells increased in both NKG2C+/NKG2A- NK cells and conventional NKG2C-/NKG2A- NK cells over time. We also observed that increased proportion of KIR2DL2/L3 single-positive/NKG2C+ NK cells correlated with higher incidence of acute graft-versus-host disease (aGVHD). Our study allows a better understanding of HLA-I/KIR interaction in the NKG2C+ NK cell education after HSCT.